Diagnostic accuracy of serum-ascites albumin gradient in esophageal varices in cirrhosis - N. C., Kiran; Thakur, Manisha Bais; Rani, Anita (International Journal of Research in Medical Sciences, 2025)
Background: Chronic liver disease (CLD) is the major global health concern. Portal hypertension leads to Esophageal Varices (EVs), when bleeds have a high mortality rate. Early diagnosis and treatment of EVs improves patient outcome and decrease mortality. The serum ascites albumin gradient (SAAG) has been used as a biomarker for detecting portal hypertension. In this study, we aimed to assess the diagnostic accuracy of SAAG in predicting EVs in cirrhotic patients. Methods: This was an observational cross-sectional study, conducted at Vardhaman Mahavir Medical College and Safdarjung Hospital, New Delhi. 75 cirrhotic patients were enrolled, SAAG was calculated and Upper GI Endoscopy was performed to screen for EVs. Diagnostic performance of SAAG was assessed using specificity, sensitivity, positive predictive value, negative predictive value and receiver operating characteristic curve (PPV, NPV and ROC) analysis. Results: The patient demographics showed a predominance of males (82.67%) with alcohol being the main cause of CLD. A strong positive correlation was found between SAAG and EVs grade. SAAG value of >1.4g/dL predicted varices with a sensitivity of 93.65%, specificity of 100%, AUC of 0.968 (p value <0.0001) and diagnostic accuracy of 94.67%. SAAG value of >1.8g/dL predicted high-risk varices with a sensitivity of 100%, specificity of 88.68% (p value <0.0001), AUC of 0.992, PPV of 78.6% (95%CI:59.0-91.7%) and diagnostic accuracy of 92.00%. Conclusions: The study shows that SAAG is a reliable marker for predicting EVs in cirrhotic patients and can be used for early identification of at-risk patients, facilitate in timely and effective management to prevent serious complications.